Manipulation of valley splitting for the WSe2/NiCl2 heterostructure by adjusting the interlayer spacing and constructing a NiCl2/WSe2/NiCl2 heterojunction. (30th October 2020) - Teng, Sukai; Mao, Xiujuan; Liu, Ze; Liu, Yang; Xu, Xiuting; Li, Linyang; Xie, Xinjian; Fan, Shanshan; Zhou, Guoxiang; Li, Jun; Li, Jia
Abstract: The electronic band structure and valley splitting of the WSe2 /NiCl2 heterostructure have been investigated by density functional theory and Berry curvature calculations. We demonstrate that the valley polarization of monolayer WSe2 is induced due to the magnetic proximity effect caused by the single layer of ferromagnetic NiCl2 . The magnitude of valley splitting depends on the stacking configurations of WSe2 /NiCl2, and the maximum value of valley splitting reaches −11.87 meV. Large valley splitting can be achieved by adjusting the layer spacing and constructing a NiCl2 /WSe2 /NiCl2 heterojunction with Ni spins arranged in parallel between two NiCl2 sheets. The valley-contrasting Berry curvature between the K and K ′ valleys suggests that the WSe2 /NiCl2 -based heterostructure could potentially be used as a valleytronic device to realize the valley-polarized anomalous Hall effect as both spin and valley filter.